TEZKİRE VE TEZKİRECİLİĞİN GELİŞİMİ / Tazkirah/Hagiography and Its Development - Küçük, Serhat (Journal of History Culture and Art Research, 2012)
Özet Arapların neseplerine olan alâkaları sebebi ile doğup gelişen tabakat kitapları, İslâm’ın geniş coğrafya ve kültürlere yayılmasıyla birlikte bu kültürlerde yerini kâriler, fakihler özellikle de şairler ve meşayihler hakkında yazılan tezkirelere bırakmıştır. Bu çalışmada tezkire, tezkireciliğin gelişimi ele alınmış, Türk edebiyatında şuarâ ve evliya tezkireciliği hakkında bilgi verilmiştir. Tespit edilebilen ve kayda değer görülen önemli tezkireler hakkında bilgi verilmiştir. Tazkirah/Hagiography and Its Development Abstract The Tabakat (hagiography) books, which came into existence and developed because of Arabs’ close interest in their ancestry, left their place to the tazkirah books about the lives of the Qur’an scholars, jurists in religion, particularly about poets and sheiks after the spread of Islam in other larger geographic and cultural areas. This study deals with the development of the tazkirahs and then gives information about poets (Shuara) and Saint (avliya) tazkirahs in Turkish literature. The study also examines some tazkirahs which are important in Turkish literature. Tazkira/Hagiographie et Son Développement Résumé Les livres d’Hagiographie qui sont nés des relations des Arabes à leurs lignages avec la propagation de l’Islam aux autres régions et cultures ont laissé la place aux hagiographies rédigés à propos des lecteurs du Coran, jurisconsultes et plus particulièrement aux poètes et soufis. Dans cette étude, nous avons examiné l’évolution de l’hagiographie et avons donné des informations à propos de la hagiographie des poètes et des saints dans la Littérature turque. Nous avons signalés les livres des Hagiographies qui méritent d’être mentionnés. ملخص كتب الطبقات التي ظھرت وازدھرت بسبب اھتمام العرب بعلم انساب تركت مكانھا لكتب التذكرة التي الشعراء والمشائخ بعد انتشار ا3س2م في أراض واسعة وبين ثقافات ٍ ِّفت في حق القراء والفقھاء وخاصةً ل ُ أ ِّدمت معلومات حول كتب مختلفة. في ھذا البحث تم تناول م ّ فھوم التذكرة، وتطور تأليف كتب التذكرة، وقُ التذكرة في الشعراء والصوفيين في ادب التركي. وقد ذكرنا أسماء كتب التذكرة التي تم العثور عليھا وكانت جديرة بالذكر